Study of the effects of silicon and sulphur foliar fertilization on yield components and yield in different winter oat cultivars - Forgács, Fanni Zsuzsa; Virág, István Csaba; Kutasy, Erika Tünde (Acta Agraria Debreceniensis, 2024)
The aim of this work was to study the effect of sulphur and silicon foliar fertilisation treatment in different Hungarian-bred winter oat cultivars on the yield and the yield components, e.g. panicle ear-1 numbers per square meters, number of panicle nodes, number of spikelets per panicle, and thousand kernel weight (TKW) in the 2022–2023 growing season. The obtained results show that the applied fertilisers influenced the measured parameters, and we get the highest yield at the combined treatment – where silicon and sulphur was both applied –, and unexpectedly the lowest when only silicon was applied during the growing period. We measured the highest number of panicles m-2 at the sulphur treated experimental plots, and the lowest at the silicon treatment. We measured the average number of nodes of the panicle, and we can say that the sulphur fertilisation caused significantly higher values than any other treatment. Talking about the spikelet numbers, we get the highest value at the sulphur fertilisation, and the lowest at the control plots. However, our result wasn’t that prominent in the case of TKW, we get the highest weight at the silicon treatment, and the lowest at the sulphur fertilisation.